OnabotulinumtoxinA Dosing, Disease Severity, and Treatment Benefit in Patients With Cervical Dystonia: A Cohort Analysis From CD PROBE - Agarwal, Pinky; Barbano, Richard; Moore, Henry; Schwartz, Marc; Zuzek, Aleksej; Sadeghi, Marjan; Patel, Atul (Frontiers in Neurology, 2022)
Introduction: The Cervical Dystonia Patient Registry for Observation of OnabotulinumtoxinA Efficacy (CD PROBE) study (ClinicalTrials.gov identifier: NCT00836017), a multicenter, prospective, observational registry, was designed to identify real-world practices and outcomes for patients with cervical dystonia (CD) treated with onabotulinumtoxinA (onabotA). This secondary analysis from CD PROBE aims to determine the impact of presentation subtype on onabotA utilization and CD severity. Materials and Methods: The study cohort includes those who completed all 3 treatments, 4 office visits, and had data recorded for all assessments. Patient outcomes were assessed with the Cervical Dystonia Impact Profile (CDIP-58), Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS), and determination of CD severity. Treatment interval, dose, and adverse events (AEs) were also recorded. Data were stratified according to prior exposure to botulinum toxins (BoNTs) and analyzed with descriptive statistics. Results: Torticollis was the most common presentation subtype in the study cohort (N = 350); the proportion of patients with torticollis was highest in those with severe disease. At each treatment, between 40.7% - 65.2% of those categorized as severe shifted to moderate or mild after treatment. Sustained improvements in CDIP-58 and TWSTRS were observed regardless of prior exposure to BoNTs. Dosing of onabotA generally increased from injection 1 to injection 3 and tended to be lower for patients naïve to BoNT. Median time interval between injections for the study cohort was 94.0 to 97.5 days. The most common AEs (dysphagia, muscular weakness) and injection intervals were similar between naïve vs non-naïve patients; there were no serious treatment-related AEs. Conclusions: This secondary cohort analysis from CD PROBE demonstrates that three repeat treatments with onabotA at intervals consistent with label attenuated disease severity and neck pain, resulting in sustained improvements in physician- and patient-reported outcomes. No new safety signals were identified.